SMALL SPORT ZONES AT HOME: INTERIOR AND DESIGN - Tasheva, Stela; Angelova, Desislava; Vodenova, Pavlina (Innovation in Woodworking Industry and Engineering design, 2022)
The report examines a growing phenomenon: (sport) exercising at home. The reasons for the ever-wider spread of this, can be found in the consequences of the Covid pandemic, but also in the changed everyday culture of society (including the digital revolution and the possibilities for remote work). The purpose of the research is to track the current needs and appropriate solutions in the creation of sports areas in small spaces, or in zones not originally meant for exercising pro-cesses. Comparative analysis and survey research are used. The expected outcomes are in the fields of design theory, contemporary design and architecture.